Treatment Switching and Discontinuation Over 20 Years in the Big Multiple Sclerosis Data Network - Hillert, Jan; Magyari, Melinda; Soelberg Sørensen, Per; Butzkueven, Helmut; Van Der Welt, Anneke; Vukusic, Sandra; Trojano, Maria; Iaffaldano, Pietro; Pellegrini, Fabio; Hyde, Robert; Stawiarz, Leszek; Manouchehrinia, Ali; et al. (Frontiers in Neurology, 2021)
Background: Although over a dozen disease modifying treatments (DMTs) are available for relapsing forms of multiple sclerosis (MS), treatment interruption, switching and discontinuation are common challenges. The objective of this study was to describe treatment interruption and discontinuation in the Big MS data network. Methods: We merged information on 269,822 treatment episodes in 110,326 patients from 1997 to 2016 from five clinical registries in this cohort study. Treatment stop was defined as a clinician recorded DMT end for any reason and included treatment interruptions, switching to alternate DMTs and long-term or permanent discontinuations. Results: The incidence of DMT stopping cross the full observation period was lowest in FTY (19.7 per 100 person-years (PY) of treatment; 95% CI 19.2-20.1), followed by NAT (22.6/100 PY; 95% CI 22.2-23-0), IFNβ (23.3/100 PY; 95% CI 23.2-23.5). Of the 184013 observed DMT stops, 159309 (86.6%) switched to an alternate DMT within 6 months. Reasons for stopping a drug were stable during the observation period with lack of efficacy being the most common reason followed by lack of tolerance and side effects. The proportion of patients continuing on most DMTs were similarly stable until 2014 and 2015 when drop from 83% to 75% was noted. Conclusions DMT stopping reasons and rates were mostly stable over time with a slight increase in recent years, with the availability of more DMTs. The overall results suggest that discontinuation of MS DMTs is mostly due to DMT properties and to a lesser extent to risk management and a competitive market.